Isolation and Selection of Plant Growth Promoting Endophytic Bacteria Associated with Healthy Hevea brasiliensis for Use as Plant Growth Promoters in Rubber Seedlings under Salinity Stress - Kulwadee Khotchanalekha (Science Faculty of Chiang Mai University, 2020)
Endophytic bacteria are defined as microorganisms that live in plant tissues for the whole or part of their lives without causing adverse effect on the host plant. Bacterial endophytes have been reported as plant growth promoters in several kinds of plants under normal and stress conditions. The aims of this study were to isolate plant growth-promoting endophytic bacteria from healthy Para rubber trees (Hevea brasiliensis) and investigate their effects on the growth of Para rubber seedlings grown under salinity stress. Among the 415 endophytic isolates obtained, isolates AP6A3 and ER212 were chosen for in vivo study under greenhouse conditions. Isolate AP6A3 produced a phytohormone indole acetic acid (IAA) at 58.39 μg/ml and ACC deaminase; it was able to fix nitrogen, having a nitrogenase activity at 64.14 μmol C2H4/tube/h determined using acetylene reduction assay but could not solubilize inorganic phosphate. Isolate ER212 strongly solubilized tricalcium phosphate and released soluble phosphate at 197.01 μg/ml; it produced only trace amounts of IAA, was absent of ACC deaminase and did not fix nitrogen. Isolates AP6A3 and ER212 tolerated salinity well, at least 7% and 10% NaCl, respectively. Characterization of these two isolates by conventional methods displayed that isolates AP6A3 and ER212 belonged to the genus Enterobacter and Bacillus, respectively. These two endophytes were then employed in greenhouse experiments with Para rubber seedlings grown under salinity stress (500 mM NaCl). Interestingly, both endophytic isolates significantly enhanced the growth (based on shoot height, stem diameter, root length, fresh and dry weight) of Para rubber seedlings when compared to the un-inoculated seedlings. These results demonstrated that the endophytic Enterobacter sp. strain AP6A3 and Bacillus sp. strain ER212 had a potential application as bio-fertilizer for plants grown in saline environments.